2023
DOI: 10.3390/medicina59010160
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the Transaxillary Access for Minimally Invasive Aortic Valve Surgery

Abstract: Background and Objectives: Transaxillary access is one of the latest innovations for minimally invasive aortic valve replacement (MICS-AVR). This study compares clinical performance in a large transaxillary MICS-AVR group to a propensity-matched sternotomy control group. Materials and Methods: This study enrolled 908 patients undergoing isolated AVR with a mean age of 69.4 ± 18.0 years, logistic EuroSCORE of 4.0 ± 3.9%, and body mass index (BMI) of 27.3 ± 6.1 kg/m2. The treatment group comprised 454 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, this explanation is highly likely to be insufficient to account for this phenomenon. Previously, we examined the feasibility of MICLATS-AVR compared to full conventional sternotomy, in which we also observed a comparable frequency of postoperative delirium syndrome (15.9%) in the sternotomy group, which did not significantly differ from that in the MICLATS-AVR group [10]. Therefore, the cause of the development of postoperative delirium syndrome appears to be also influenced by other circumstances that were not the primary focus of this study, as they do not align with the primary research question.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, this explanation is highly likely to be insufficient to account for this phenomenon. Previously, we examined the feasibility of MICLATS-AVR compared to full conventional sternotomy, in which we also observed a comparable frequency of postoperative delirium syndrome (15.9%) in the sternotomy group, which did not significantly differ from that in the MICLATS-AVR group [10]. Therefore, the cause of the development of postoperative delirium syndrome appears to be also influenced by other circumstances that were not the primary focus of this study, as they do not align with the primary research question.…”
Section: Discussionmentioning
confidence: 65%
“…The field has witnessed a transformation, with surgical aortic valve replacement now amenable to minimally invasive techniques, such as sternum-sparing thoracotomies or partial hemisternotomies. Numerous studies comparing these techniques with conventional sternotomy have consistently demonstrated clear advantages, extending beyond anticipated results and cosmetically desirable outcomes [10,[15][16][17]. This not only underscores the efficacy of minimally invasive approaches but also emphasizes the undeniable patient preference for methods that reduce discomfort, expedite recovery, and enhance cosmetic results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transaxillary group had longer operative times but reduced blood transfusion, ventilator time, wound complications, and intensive care and hospital LOS. This approach provided at least equivalent outcomes to full sternotomy AVR with excellent cosmesis and unrestricted postoperative physical activity due to the lack of sternotomy or rib spreading [11 ▪ ]. All three trials concluded that the MICS approach provided comparable results to full sternotomy with less trauma.…”
Section: Minimally Invasive Cardiac Surgery – Recent Trialsmentioning
confidence: 89%
“…As previously described [11,12], under general anaesthesia, right jugular vein was cannulated before surgical draping. The cardiopulmonary bypass was conducted maintaining normothermia after cannulation of the common femoral artery and the femoral vein, using the Seldinger technique and TOE guidance after surgical cut-down.…”
Section: Trans-axillary Accessmentioning
confidence: 99%